A3.21 MicroRNA-34a and microRNA-155 in Systemic Sclerosis: possible epigenetic biomarkers of endothelial dysfunction in VEDOSS and long-standing disease. (31st January 2014) - Alivernini, Stefano; Laura Bosello, Silvia; De Luca, Giacomo; Canestri, Silvia; Di Mario, Clara; Rita Gigante, Maria; Tolusso, Barbara; Ferraccioli, Gianfranco
Abstract : Background and Objectives: MicroRNAs (miRs) are a novel class of post-transcriptional regulators that have been implicated in the pathogenesis of Systemic sclerosis (SSc). MiR-34a and miR-155 were found to be related to endothelial senescence and inflammation. The aim of this study was to investigate the expression of miR-34a and miR-155 in peripheral blood mononuclear cells (PBMCs) in SSc. Methods: Twenty-seven consecutive patients with Raynaud phenomenon (RP) were enrolled in this exploratory study. Particularly, patients were divided into 3 different study cohorts: patients with primary RP with normal capillaroscopic findings and without any autoantibodies (n = 8), SSc patients fulfilling the Very Early Diagnosis Of Systemic Sclerosis (VEDOSS) criteria (n = 9) and SSc patients fulfilling the 1987 ACR criteria (n = 10) respectively. Gender and age matched healthy individuals (n = 7) were enrolled as controls. Expression of miR-34a and miR-155 was evaluated by qPCR on PBMCs isolated by gradient hystopaque technique from peripheral blood (PB) of all patients. To identify miR-34a HumanTargetScan cross-referenced was employed. Identified targets were experimentally verified by qPCR. VEGF, VEGF-RII, IL-6 and IL-6R plasma levels were determined through ELISA. Results: MiR-155 is overexpressed either in VEDOSS (p = 0.0002) and SSc (p = 0.04) patients compared to healthy controls. MiR-34a expression is increased only in SSc compared to healthy controls (p = 0.01). Patients with primary RP did not differ according to miR-155 and miR-34a expression from healthy controls (p>0.05) Dividing SSc and VEDOSS patients according to the autoimmune profile, anti-Scl70 + have higher expression of miR-34a compared to anti-centromere + patients (p = 0.04). Furthermore, stratifying SSc patients according to the clinical vascular manifestations, SSc patients with active and/or previous digital ulcers have significantly higher miR-34a expression compared to patients without ulcers history (p = 0.01). Finally the expression of miR-34a directly correlated with the skin score value (R = 0.52, p = 0.032) in both SSc and VEDOSS patients and with IL-6 plasma levels (R = 0.42, p = 0.01). Using HumanTargetScan cross-referenced methodology, IL-6 receptor (IL6-R) was selected as target of miR-34a. IL6-R gene expression was found to be significantly higher in VEDOSS compared to SSc patients (p = 0.02). VEGF plasma levels were significantly higher in SSc patients compared to healthy controls (p = 0.01) as well as IL-6 plasma levels (p = 0.02), whereas no significant differences were found in VEGF-RII and IL-6R plasma levels comparing the different patients' cohorts. Conclusions: Epigenetic factors, as miR-34a and miR-155 are deregulated in SSc and VEDOSS. Their expression analysis could help to differentiate different disease phases and between primary and SSc associated RP.